2021
DOI: 10.1029/2020ef001857
|View full text |Cite
|
Sign up to set email alerts
|

How Much Heat and Salt Are Transported Into the South China Sea by Mesoscale Eddies?

Abstract: Eddy-induced transport through the Luzon Strait critically affects the physical and biological properties of the South China Sea (SCS). The eddy-induced volume, heat and salt transport are comprehensively evaluated based on the South China Sea Physical Oceanic Dataset (SCSPOD) observations. To avoid the bias involved in extreme eddy events, 76 shedding anticyclonic eddies, 46 shedding cyclonic eddies, 29 locally formed anticyclonic eddies and 40 locally formed cyclonic eddies from 1993 to 2018 are taken into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…EKE maps are computed using the formula EKE = 1 2 (u 02 g +v 02 g ) where u 0 g and v 0 g indicate meridional and zonal geostrophic velocity anomalies, respectively. To date, studies have confirmed the capability of eddies to transport saline Kuroshio water into the SCS (Jia and Liu, 2004;Zhang et al, 2017;Yang et al, 2019;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…EKE maps are computed using the formula EKE = 1 2 (u 02 g +v 02 g ) where u 0 g and v 0 g indicate meridional and zonal geostrophic velocity anomalies, respectively. To date, studies have confirmed the capability of eddies to transport saline Kuroshio water into the SCS (Jia and Liu, 2004;Zhang et al, 2017;Yang et al, 2019;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
“…This salt water moves along the northern slope of the basin, extending as far as the southeastern part of Hainan Island (Wang et al, 2015;Yi et al, 2020). Eddies can mix this part of the saltwater in the upper layer while moving northwestward, which has been confirmed as a key dynamic player in introducing and redistributing this Pacific water mass into the SCS (Yang et al, 2021).…”
Section: Distribution Of Monopole and Dipole Modesmentioning
confidence: 92%
See 1 more Smart Citation
“…These anomalies quantify how much T and S vary when following an isopycnal. They are used to quantify the amount of heat and salt transported by the eddy (Laxenaire et al, 2019;Y. Yang et al, 2021).…”
Section: Potential Density Field Decompositionmentioning
confidence: 99%
“…An eddy can be intuitively defined as a region of instantaneous streamline spiraling around a central point [1,2]. The vertical depth of eddies has a wide-ranging impact, as it can bring cold water and nutrients from the deep ocean to the surface or push warm surface water into deeper ocean layers [3], thus affecting the ocean's mixed layer, density stratification, and even deeper ocean dynamics [4][5][6][7]. In oceanography, eddies with radii on the order of the first baroclinic Rossby radius and lasting for days to months are referred to as mesoscale eddies, while eddies with radii smaller than the first baroclinic Rossby radius but larger than the boundary layer turbulence scale and lasting for hours to days are called submesoscale eddies [8,9].…”
Section: Introductionmentioning
confidence: 99%